Simvastatin Encapsulation in Alginate-Based Microspheres - Parsian, Ava (Université d'Ottawa / University of Ottawa, 2016)
Despite the great success of hip implant surgeries, wear particle-induced implant aseptic loosening still limits the implant longevity. Simvastatin, an FDA-approved cholesterol lowering statin, is a promising drug candidate for the treatment of implant aseptic loosening due to its anti-inflammatory properties as well as its ability to stimulate bone growth and inhibit bone resorption. In addition, alginate microspheres have been used extensively in drug delivery applications because of alginate properties, including biocompatibility and gelation in mild conditions. However, the hydrophobicity of simvastatin, as well as the large alginate microsphere pore size leading to the leakage of low molecular weight drugs are limiting factors for their use as a delivery system for simvastatin. Therefore, the objectives of this thesis were twofold: 1. To complex simvastatin with 2-hydroxypropyl-β-cyclodextrin (HP-βCD) in order to increase its solubility; and 2. To increase simvastatin encapsulation efficiency in alginate microspheres by coating the microspheres with chitosan, adding dextran sulfate in the alginate solution, and optimizing the gelation conditions used for the synthesis of the microspheres (e.g., volume of gelation medium, curing time, and addition of simvastatin in the gelation medium). Results showed that simvastatin complexation with HP-βCD increased with HP-βCD to simvastatin molar ratio, to a maximum of 97.6% at the molar ratio of 10. Results also showed that chitosan coating of the alginate microspheres increased simvastatin encapsulation efficiency (up to 10.6%), which was further improved (up to 14.0%) when adding 2.0% (w/v) dextran sulfate to the alginate solution. This increase was likely due to electrostatic interactions between dextran sulfate and chitosan in addition to alginate, resulting in a denser coating. Finally, the addition of simvastatin in the gelation medium was shown to also increase simvastatin encapsulation (up to 22.4%), likely because of a decrease in the diffusion of simvastatin out of the microspheres. Overall, this work completed the initial steps for the development of an alginate-based drug delivery system for simvastatin with the long-term goal of providing a local delivery of simvastatin to modulate implant aseptic loosening.
Keywords: Drug Delivery System; Alginate; Microspheres; Encapsulation; Simvastatin